ANALISIS SISTEM KEBIJAKAN PENGEMBALIAN KELEBIHAN PEMBAYARAN WAJIB PAJAK ORANG PRIBADI MELALUI RESTITUSI DAN KOMPESANSI DI KPP PRATAMA MANADO - Lempas, Bryan S; Runtu, Treesje; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Tax is a source of revenue to finance all State expenditures including expenditures for development and expenditure in improving the welfare and quality of Human Resources (HR). The tax contribution in funding State expenditures continues to increase and requires support in the form of raising public awareness to meet its tax obligations. This research was conducted in Manado City, where this study aims to examine the return of overpayment. The research method used is descriptive analysis research. Result of research indicate that KPP Pratama manado give good service for taxpayer individual who apply for restitution of amount of tax debt paid by public also must know that even if money have entered to treasury state if proved there is more pay then State treasury also willing to reverse or compensate for other types of taxes. The refund of the tax payment is a refund of tax overpayment that has been assumed is really a tax that is more paid.Keyword : Refund of overpayments, restitution, and compensation of individual taxpayers